Characterization of PlyPl23, an endolysin from a Paenibacillus larvae bacteriophage - Oliveira, Ana Cristina Afonso (2014)
EMBO Conference on Viruses of Microbes III: Structure and Function - from Molecules to Communities (Programme and Abstract Book)